2016
DOI: 10.1038/srep32170
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Modeling of Short and Medium Range Order in Amorphous Ta2O5 Thin Films

Abstract: Amorphous films and coatings are rapidly growing in importance. Yet, there is a dearth of high-quality structural data on sub-micron films. Not understanding how these materials assemble at atomic scale limits fundamental insights needed to improve their performance. Here, we use grazing-incidence x-ray total scattering measurements to examine the atomic structure of the top 50–100 nm of Ta2O5 films; mirror coatings that show high promise to significantly improve the sensitivity of the next generation of gravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 51 publications
4
40
0
Order By: Relevance
“…The polyhedra are predominantly distorted octahedra (∼80% for Ta, ∼60% for Zr, [10]). It has been shown that the first peak of GðrÞ for pure a-Ta 2 O 5 closely resembles the corresponding peak of crystalline Ta 2 O 5 [15]. We find that the coordination of Ta by O (n TaO ) is 6.13 whereas n ZrO is 6.14; both values are for as-deposited sample.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…The polyhedra are predominantly distorted octahedra (∼80% for Ta, ∼60% for Zr, [10]). It has been shown that the first peak of GðrÞ for pure a-Ta 2 O 5 closely resembles the corresponding peak of crystalline Ta 2 O 5 [15]. We find that the coordination of Ta by O (n TaO ) is 6.13 whereas n ZrO is 6.14; both values are for as-deposited sample.…”
supporting
confidence: 53%
“…Further details on the GIPDF data collection method and its merits, in particular pertaining to doped tantala coatings, are discussed in Ref. [15]. The total scattering data were reduced to the normalized structure factor SðqÞ after applying identical corrections on all samples for air scattering, absorption, Compton scattering, polarization effects, and geometric effects due to the detector footprint [15][16][17].…”
mentioning
confidence: 99%
“…In order to explain the impact of stress relaxation on energy loss one has to consider that the measurement were done only at room temperature, hence, only the reduction of TLS density having a barrier height of about 0.5 eV is probed. Energy barriers of interest at room temperature correspond to equilibrium configurations formed by several PSUs, as suggested in a recent work 19,41 . The recent observations of ref.…”
Section: Discussionmentioning
confidence: 83%
“…It might be correlated with the short‐range order of amorphous TNO films. The annealing process may increase the cross‐linking of primary structural unit to improve the poor short‐range order in an amorphous material . The lowest states in conduction band are localized if the short‐range order of amorphous TNO decreases.…”
Section: Resultsmentioning
confidence: 99%
“…The annealing process may increase the cross-linking of primary structural unit to improve the poor short-range order in an amorphous material. 12 The lowest states in conduction band are localized if the short-range order of amorphous TNO decreases. This might be due to the effect of scattering which is related to the amorphization of TNO films annealed at low temperature.…”
Section: Resultsmentioning
confidence: 99%